2013
DOI: 10.1371/journal.pone.0072032
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Androgen Deprivation on Cerebral Morphometry in Prostate Cancer Patients – An Exploratory Study

Abstract: BackgroundAndrogen deprivation therapy (ADT) is a common treatment for non-metastatic, low-risk prostate cancer, but a potential side effect of ADT is impaired brain functioning. Previous work with functional magnetic resonance imaging (MRI) demonstrated altered prefrontal cortical activations in cognitive control, with undetectable changes in behavioral performance. Given the utility of brain imaging in identifying the potentially deleterious effects of ADT on brain functions, the current study examined the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
75
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(82 citation statements)
references
References 38 publications
(36 reference statements)
5
75
2
Order By: Relevance
“…35 While not all studies support this connection, 6 there is an indication that ADT decreases cognitive function 79 , brain function 10 and neuronal structure in humans, all of which are prodromal indices of progressive cognitive decline and possible AD. 11 The disease mechanism of AD is unknown, and complex. However, several side effects and impacts of ADT are known to be involved in proposed AD disease mechanisms including loss of testosterone and estradiol.…”
Section: Introductionmentioning
confidence: 99%
“…35 While not all studies support this connection, 6 there is an indication that ADT decreases cognitive function 79 , brain function 10 and neuronal structure in humans, all of which are prodromal indices of progressive cognitive decline and possible AD. 11 The disease mechanism of AD is unknown, and complex. However, several side effects and impacts of ADT are known to be involved in proposed AD disease mechanisms including loss of testosterone and estradiol.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggest that ADT use may be associated with structural and functional changes in brain areas relevant to dementia 14151617. Some studies have suggested that the use of ADT might cause the impairment of cognitive function, which is one of the common symptoms of dementia; however, the association between ADT and cognitive impairment still remains controversial 181920212223.…”
Section: Introductionmentioning
confidence: 99%
“…So far, only a few studies have explored biomarkers and other potential correlates of cognitive functioning in hormone therapy patients. For example, investigators have examined neuronal activation in ADT patients and have found altered activation patterns [62, 63] and changes in brain structure [64]. However, until there is more definitive evidence regarding the association between hormone therapy use and cognitive impairment, investigations into neurobiological and pathophysiological mechanisms should, in our opinion, be secondary or an adjunct to well controlled neuropsychological studies.…”
Section: Discussionmentioning
confidence: 99%